From Social Responsibility to “Civic University”: The Case of Mariupol State University - Анастасія Трофименко (Університети і лідерство, 2023)
The essence of the “civic university” as the highest manifestation of the social role of the institution of higher education has been defined and analysed in the article. It has been established that the social mission of the university can have various forms and vectors of practical implementation; they include educational, research, socio-cultural, ethical, economic dimensions, social support of students and employees, development of social dialogue, charity and volunteering, internationalisation.